PEMBERDAYAAN MASYARAKAT PESISIR MELALUI PENGEMBANGAN USAHA AGRIBISNIS PERDESAAN DAN IMPLIKASINYA TERHADAP KETAHANAN EKONOMI KELUARGA (Studi di Desa Glagah Kecamatan Temon Kabupaten Kulon Progo ) - , Nurman Wikanto Purnomo ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research conducted based on the problems about the important of developing effort of coastal area society. The condition of coastal area society at Glagah village in which most of them are farmers should not get similar way of treatment to others. It is not separated to environment condition and potential in Glagah coastal area. Most of societies at Glagah tend to be chiliâs farmer at the coastal area. Developing effort program is called agribusiness effort development. This research aims to know implementation of rural agribusiness effort development at Glagah Village and to know the implication of it to family economy resilience. This research constitute survey study and uses descriptive research model with qualitative and quantitative approaches. Technique of sample taking uses probability sampling in the amount 45 farmers as Gapoktan members of Glagah Sari, Glagah Village Temon Sub District Kulon Progo Regency. Technique of data collection is done by using observation participation, questioner, intensive interview, and librarian study. The result of this study shows that Rural Agribusiness Effort Development Program run well at Gapoktan Glagah Sari. It can be seen from suitable fund distribution, PUAP aid fund is always developing, assistance also be able increase farmersâ capability, and farming institution are more developed. While, the implication of PUAP Program to family economy resilience only has low effect for farmersâ income. It is caused of the low of fund aid received by farmers.